Social security reform in advanced countries : evaluating pension finance - Ihori, Toshihiro; Tachibanaki, Toshiaki (New York : Routledge, 2002)
This book brings together internationally-renowned scholars to evaluate the effect of recent social security reforms in advanced countries (pension programmes in particular) and to suggest policy reforms for the future.
Papers presented at the conference at the University of Tokyo in September, 1998.
Includes bibliographical references and index.
oif 04/08/16
Loan
Keywords: Social security; Social security; Privatization; Pension trusts